Mental state of hemodialysis patients and treatment - Hirayama, Nobuaki; Suzuki, Tadashi; Kaneko, Tadashi; Uematsu, Waka; Funyu, Tomihisa; Osanai, Sachi (Jinko Toseki Kenkyukai kaishi. [Journal of the Dialysis Research Society, 1985)
Because of a desire to provide the most suitable treatment for hemodialysis patients, psychological, physical and social problems influencing the mental state of the patients were studied. One hundred in-hospital hemodialysis patients were divided into groups according to age, presence of family problems, occupation, physical complications and character, and compared. The mental state was most favorable between 3 and 12 months after the introduction of hemodialysis, whereas in patients with hemodialysis for other lengths of time, depression was noticed in more than half of the subjects. In most of the patients, irritation and anger, and loss of brightness or sympathy were observed during the first 3 months or later than 12 months after introduction of the therapy respectively. As for the relationship between age and mental state most of the patients between 26 and 40 years of age showed depression, irritation, anger, pessimism, despair, fear of death and aggression. Regarding family problems, psychopathology including loss of brightness or sympathy, pessimism, despair, anger and aggression was common in divorced, persons and those having children younger than 18 years. As to occupation, most of the salaried workers showed depression, irritaion and anger, whereas most of the unemployed patients presented despair, pessimism and loss of brightness or sympathy. The patients with physical complications other than chronic renal failure showed various psychic problems including a suicidal tendency. Analysis of the character tendency by the Yatabe and Gilford test revealed that B-type character was associated with an increased probability of showing depression, pessimism, anger and aggression. A person of E-type character was likely to show despair and a suicidal tendency and C-type despair and fear of death, whereas a D-type person was most unlikely to experience psychic problems. The patients were treated mainly with psychotrophic drugs such as antidepressants and/or minor tranquilizers together with psychiatric interviews. Some of the patients, however, needed to have the necessity of hemodialysis explained repeatedly and/or required consecutive psychotherapy. Psychotherapy clearly diminished the psychological or psychiatric symptoms in some of them. The present study suggested that a poor outcome of a psychological condition after the introduction of hemodialysis is indicated by 1) a spouse who cannot cope, 2) symptoms of physical origin, 3) the absence of full-time work, 4) having one or young children, 5) being in the prime of life, 6) B and E types of character and 7) long duration of therapy. The study emphasizes the importance of psychological and social care in the overall management of patients under hemodialysis therapy.